Evaluating the need for first aid and basic life support training among early childhood development practitioners in Cape Town, South Africa - Evans, Derrick Reginald (Division of Emergency Medicine, 2016)
Background: Unintentional injury remains one of the leading causes of morbidity and mortality among children worldwide. The aim of this study will be to ascertain if teachers and teacher's assistants in early childhood development facilities have training in first aid or emergency care, what their attitudes towards first aid are and how competent they feel to manage emergencies. Methods: A cross-sectional survey will be carried out among early childhood development (ECD) practitioners who are studying at the Goodwood campus of Northlink College in the Western Cape. The survey will be optional and anonymous. A standardised collection of demographics will be performed and participants will be given a questionnaire that assesses the participant's knowledge and attitudes towards first aid and basic life support.